THE EFFECT OF ORGANIZATIONAL CHARACTERISTICS AND ENVIRONMENTAL CHANGES ON THE CREATION OF ENTREPRENEURSHIP FOUNDATION THROUGH INDIVIDUAL CHARACTERISTICS VARIABLE (CASE STUDY ON SMEs IN PALEMBANG CITY) - Rasyid, Nirwan; Burhan, Hanifati; Mandiangan, Pridson (International Journal of Social Science and Business, 2018)
The objective of this study was to determine the effect of organizational characteristic and environmental change on the creation of entrepreneurial foundation through individual characteristic variables (case studies on SMEs in Palembang City). The research design was causal study. The type of data used in the form of primary data, namely the questionnaire. The sampling technique used was purposive sampling. Based on the criteria obtained Total sample of SMEs as many as 101 people. Data analysis technique used was path analysis method. By conducting path analysis for direct effect, indirect effect, and total effect. The results of the study stated: 1. Characteristics of the organization had a significant positive effect on individual characteristics (first hypothesis accepted), 2. Changes in the business environment had a significant positive effect on individual characteristics (second hypothesis accepted), 3. Organizational characteristics had a significant positive effect on the creation of organizational entrepreneurs SMEs ( the third hypothesis was accepted), 4. Changes in the business environment had a significant positive effect on the creation of the organizational entrepreneurs of SMEs (fourth hypothesis accepted), 5. The individual characteristics had a significant positive effect on the creation of the organizational entrepreneurs of SMEs (the fifth hypothesis accepted), 6. Organizational characteristics, individual characteristics, and environmental changes have a significant positive effect on the creation of organizational entrepreneurs of SMEs (6th hypothesis accepted), 7. Organizational characteristics and environmental changes had a significant positive effect on the creation of organizational entrepreneurs of SMEs through individual characteristics as intervening variables (the seventh hypothesis accepted).